Identification Method of Evolution Patterns of Favorable Oil and Gas Channels at Source Fault Configuration and Its Application - Bowei, Zhang; Guang, Fu (Frontiers in Earth Science, 2022)
Favorable oil and gas channels during fault activity and cease episodes were determined to understand oil and gas distribution in reservoirs of "lower generation, upper accumulation" type near faults in petroliferous basins through identifying and coupling conduit systems and hydrocarbon expulsion distribution during these periods, respectively. It was used to establish a method to identify evolution patterns of favorable oil-gas charging positions at source-fault configurations, which was applied to understand the evolution of favorable oil and gas channels in the middle and lower Es-3 sub-member in the southwest of Jiuzhou fault. Results show that the conduit pattern in the Es3 sub-member is mainly distributed in the center, west and east of the F1 fault and the eastern of the F7 fault in the southwest of the Jiuzhou fault. The conduit to non-conduit pattern is mainly distributed in the middle and center of F7 fault. The non-conduit to conduit pattern is mainly distributed in the west and east of the F1 fault and the east of the F7 fault. The non-conduit is mainly distributed in the middle and east of F7 fault. The conduit pattern and conduit to non-conduit pattern in the middle and lower Es-3 sub-member are favorable for hydrocarbon migration and accumulation. It is consistent with the oil and gas discovered in the middle and lower Es-3 sub-member near the southwest of The Jiuzhou fault, indicating that this method is feasible to identify the favorable oil and gas channels at source-fault configurations.